THE SCIENTIFIC- PHILOSOPHICAL CONCEPT OF READING. (World Bulletin of Social Sciences, 2024)
In this article, it is stated that reading is a complex and multifaceted concept, that reading is a necessary attribute of human spiritual existence as a selforganizing synergistic phenomenon